Pengaruh Religiosity dan Social Dominance Orientation terhadap Dukungan Perempuan pada Benevolent Sexism - Nazwa Rahman; Miftahun Najah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Gender inequality persists not only through overt discrimination but also through subtler ideologies such as benevolent sexism, which idealizes women as needing men's protection while reinforcing dependency on traditional gender roles. Women often endorse this seemingly positive form of sexism, yet the psychological factors underlying such support remain underexplored, particularly in collectivistic, Muslim-majority societies such as Indonesia, where religiosity and orientation toward social hierarchy shape daily life. Prior studies have examined religiosity and social dominance orientation separately, while research integrating both constructs to explain Indonesian women's support for benevolent sexism remains limited. This study examined the effects of religiosity and social dominance orientation on women's support for benevolent sexism using a quantitative cross-sectional design. Participants were 205 women aged 18–25 years, mostly active university students, selected through purposive sampling. Data were collected using the Centrality of Religiosity Scale, the Short Social Dominance Orientation Scale, and the Benevolent Sexism subscale of the Ambivalent Sexism Inventory, then analyzed through multiple linear regression in Jamovi. Results showed that religiosity (B = 1.12, p < .001) and social dominance orientation (B = 1.20, p < .001) each positively and significantly predicted support for benevolent sexism. Together, the two variables simultaneously accounted for 72.4% of the variance in benevolent sexism (R² = .724, F(2, 202) = 266.00, p < .001). These findings indicate that women's acceptance of benevolent sexism is shaped by the centrality of religious values and preference for social hierarchy, not merely individual disposition. This study contributes to social psychology, psychology of religion, and gender studies, with practical implications for gender equality education engaging religious leaders and communities.